Development of underground structure case study: additional car parking space at Sogo complex / Nur Syaimira Mat Rosli - Mat Rosli, Nur Syaimira (2010)
Development of underground structures is a rare development in Malaysia. Underground development is often associated with high in development costs. For other countries that have high growth, the development of underground structure has become an option in development. In addition, roads were built below the surface in the various countries. However, in Malaysia the development of underground structure is often seen as the development of car parking space. The development is often built for commercial buildings. Because of this, author want to conduct a research related to the development of underground structure. This research will focus on basic considerations of development of a joint venture between the government and private sectors in relation the development of underground structure. Beside that, the consideration of approval by the authority regarding to the development of underground structure will focus by author. To achieve the objectives of the study, the author will use both survey instruments. This is based on data collection study. Finally, author will proposed a recommendation and conclusion have been made as a result of analysis of data obtained.